2018
DOI: 10.24875/ric.18002474
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Lung and Joint Involvement in Patients with Rheumatoid Arthritis and Interstitial Lung Disease: A Cross-Sectional Study

Abstract: We only found a good correlation between ESR and ground glass score. It is possible that different pathways of the immune response mediate damage in lungs and joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
5
0
2
Order By: Relevance
“…If simple spirometry is used, these patients cannot be identified. In our work those patients with lung disease presented higher rates of inflammatory serological markers, such as ESR and CRP, in line with previous studies [14][15][16][17] . In our study, higher values of CRP and ESR at RA diagnosis associated a DLCO decrease over time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…If simple spirometry is used, these patients cannot be identified. In our work those patients with lung disease presented higher rates of inflammatory serological markers, such as ESR and CRP, in line with previous studies [14][15][16][17] . In our study, higher values of CRP and ESR at RA diagnosis associated a DLCO decrease over time.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, higher values of CRP and ESR at RA diagnosis associated a DLCO decrease over time. The presence of inflammatory proteins in the lungs has been associated with progressive lung disease 16 and higher rates of ESR associate ground glass opacities on lung HRCT 15 . Sparks et al reported a higher risk for the development of RA-ILD in patients with higher values of DAS28 in a prospective cohort of RA patients 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Females with rheumatoid arthritis older than 60 years of age were found to be associated with significantly higher prevalence of gall stones compared with general population and the most probable reason is hyperlipidemia and chronic inflammation. 13 The other co-morbidities with cholelithiasis include Crohn's disease, ileal resection or other diseases of ilium, hence it is important to know the frequency of gall bladder diseases which might provide the clue about comorbidities as well.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study investigating joint and lung involvement in patients with RA-ILD reported a good correlation between the ESR and the ground glass score of HRCT images of the lungs. 20 …”
Section: Discussionmentioning
confidence: 99%